The Relationship Between Work Stress Among Teachers and Technological Advancements in Education: The Impact of Artificial Intelligence on the Role of Schoolteachers in the Sultanate of Oman (Journal of Education and Development, 2025)
The rapid integration of Artificial Intelligence (AI) in education is reshaping the roles of educators and their professional environments. This study examines the relationship between work stress and technological advancements among teachers in the Sultanate of Oman, focusing on the impact of AI. It explores how AI influences teachers' workloads, perceptions, and levels of stress, while identifying strategies to alleviate stress and enhance professional competence. A mixed-methods approach was employed, involving quantitative and qualitative analyses of responses from 1,500 teachers sampled using purposeful and snowball techniques. The findings indicate that AI reduces administrative burdens, enhances personalized learning, and supports professional development, but also introduces stress due to insufficient training, infrastructure limitations, and ethical concerns. Teachers with positive perceptions of AI reported lower stress levels, highlighting the importance of fostering AI literacy. Recommendations include targeted professional development, improved access to AI tools, and culturally responsive integration strategies. These findings align with Oman's Vision 2040, emphasizing innovation in education while safeguarding teacher well-being.